Posaconazole therapy in children with cystic fibrosis and Aspergillus-related lung disease. (16th March 2019) - Patel, Deepa; Popple, Sarah; Claydon, Alison; Modha, Deborah E; Gaillard, Erol A
Abstract: There is emerging evidence for the role of posaconazole in the management of Aspergillus -related cystic fibrosis (CF) lung disease. The tolerability and efficacy of posaconazole in paediatric CF is not well established. We report a prospective study over a fifty-three month period evaluating the safety, tolerability, and efficacy of posaconazole in pediatric CF. Fourteen children (seven males, median age 13 years, range 3–17 years) received a total of twenty-three courses of posaconazole (13 oral suspension and 10 tablet formulation). Of these patient episodes, nine received posaconazole for emerging or active allergic bronchopulmonary aspergillosis (ABPA) and two required a combination of posaconazole and systemic corticosteroids for difficult-to-treat ABPA. A subgroup of patients ( n = 12) with persistent isolates of Aspergillus fumigatus, in the absence of serological markers of ABPA, received posaconazole monotherapy for pulmonary exacerbations not responding to conventional broad-spectrum antibiotic treatment. Posaconazole levels, full blood count, electrolytes, and liver function were monitored on day 7 of treatment and then monthly. Posaconazole was well tolerated in all but three patients. Therapeutic plasma levels >1 mg/l were achieved in all receiving the tablet formulation in comparison to 60% on the liquid preparation. There was a modest but significant improvement in FEV1 (% predicted) demonstrated for the cohort as a whole ( p = 0.015) following posaconazole therapy. Posaconazole is well tolerated in children as young as six years old, improvements in lung function are observed, and therapeutic plasma levels are readily achieved in patients taking the tablet formulation and in adherent patients taking the liquid formulation.